Apa yang direkomendasikan apoteker untuk tatalaksana diare akut pada anak? Sebuah survei di wilayah timur Kota Surabaya - Linda Fidya Ningsih; Adji Prayitno Setiadi; Abdul Rahem; Cecilia Brata; Yosi Irawati Wibowo; Eko Setiawan; Steven Victoria Halim (Faculty of Pharmacy, Universitas Gadjah Mada)
Appropiate recommendation provided by pharmacists is considered as a crucial factors to prevent morbidity and mortality among children with acute diarrhea in the community. This study aimed to determine the type and the appropriateness of recommendations provided by the community pharmacists in the eastern part of Surabaya to children presenting with acute diarrhea. This was cross-sectional study conducted by using a questionnaire consisting of questions about participants’ characteristics and a case of acute diarrhea in children without complications and other “alarm symptoms” requiring medical referral. The appropriate recommendation for the case was to give a combination of oral rehydration solution (ORS) and zinc with or without other recommendations. Data were analyzed descriptively using SPSS version 22. A total of 84 pharmacists provided consent to be participants in this study. The majority of participants (73,81%) were pharmacists manager and more than 50% of them completed pharmacist professional degree between 2010 and 2019. Type of pharmacists’ recommendations were further classified as: medical referral, provision of medicine, laboratory testing, and non-pharmacology treatment. The most provided recommendations were provision of medicine (97,62%) with or without other recommendations. Medical referral were recommended by 22 pharmacists (26,19%). Of the total participants, 13,09% provided appropriate recommendations. Findings of this study indicate the necessity to optimise the role of community pharmacists in managing acute diarrhea in children. Further study to identify the needs of community pharmacists, either conducted with qualitative or quantitative approach, is required as the key step before implementing further intervention.